Analysis of amino acids for detection of pork in fresh and cooked meat by high performance liquid chromatography for halal authentication - Jorfi, Ramin (2012)
Many religions have some strict requirements about what should be used as food. In Islam, foods containing ingredients from pig sources are haram (unlawful) for the Muslims to consume. In the current global world, therefore, a reliable method to detect pork adulteration is needed to protect Muslim consumers from intentional or non-intentional fraud. Among the various analytical methods, high performance liquid chromatography (HPLC) has been widely used in many food authentication studies. In the current study, reverse phase high performance liquid chromatography (RP-HPLC) with ultraviolet (UV) detection system and pre-column derivatization with o-phthaldialdehyde (OPA) and 3-mercaptopropionic acid (3MPA) was applied to detect the presence of pork in beef, chevon, chicken and mutton at three different forms of raw, cooked and mixed meats. The identity and quantity of the amino acids were assessed by comparison of the retention times and peak areas of the standard amino acids. The results of this study showed that VAL, SER, ALA, HIS and ARG can be used to distinguish raw pork from the other meat types. However, analyzing the cooked meats revealed that ASP, THR and TYR are potential markers for pork adulteration. In addition, it was observed that crude protein (CP) percentages of the raw meats were not changed significantly after cooking. Regarding the mixed meats, analysis of the results showed that 10-90% pork adulteration in beef can be identified using the CYS and CP as markers. Nonetheless, this was not the same in other types of meat in that VAL and CP for chicken and VAL and phenylalanine for mutton showed potential as markers of 10-90% pork adulteration. There were no amino acids identified as a marker of pork adulteration in chevon. However, PHE may consider as a relative indicator of pork adulteration in chevon in only percentages of more than 20%. In conclusion, the results of the current study indicate that amino acid profile analysis using RP-HPLC can be employed as a marker for pork adulteration in beef,chevon, chicken and mutton in both forms of raw and cooked. With regards to the raw and mixed meat analysis, it can be concluded that VAL is a potential marker to distinguish pork adulteration in mutton and chicken. Further studies needed to find an appropriate marker in case of the beef and chevon. Moreover, ASP, THR and TYR appeared to be good markers of pork adulteration in cooked beef, mutton, chevon and chicken.